Fuzzy TOPSIS method in supplier selection and application in the garment industry - (:unkn) unknown (Lukasiewicz Research Network - Institute of Biopolymers and Chemical Fibres, 2012)
In today's world where intensive competition exists between enterprises, it is of great importance to work in cooperation with the right suppliers. Selection of the right suppliers is a significant factor in the success of enterprises. In the selection of the best supplier (s), the strengths and weaknesses of potential suppliers should be taken into consideration. Many qualitative and quantitative criteria are included in this selection process as well as the decision-maker. One of the issues that leaves the decision maker in a difficult position is selecting the most appropriate one from the alternatives available, as traditional methods may not produce a realistic solution in this process. However, multicriteria decision making methods facilitate the process of finding a solution and enable decision makers to reach the right decisions. In this study, the fuzzy TOPSIS method, which is one of the multi-criteria decision making methods, is used in this problem area to select the most appropriate supplier of garment 'X' operating in Turkey. It is detected through analyses conducted in line with the results obtained. The ranking of the three supplier firms determined by firm X are as follows in terms of closeness index values: supplier 1, supplier 3 and supplier 2.
Keywords: Fuzzy TOPSIS; Multicriteria decision making; Supplier selection; Textil industry